Fatores determinantes da variação dos níveis séricos de BNP após valvuloplastia percutânea na estenose mitral reumática - Willian Antonio de Magalhães Esteves (2010)
Rheumatic disease is a complication of rheumatic fever that develops severe disabilities, causing reduction of life expectance of patients and leading to increasing of the economic and social costs. It is a main etiology of acquired cardiopathy in children and young adults in developing countries. The more frequent valve lesion in this disease is mitral stenosis which presents as an isolated lesion in 25% of the cases. Percutaneous mitral valvuloplasty became the treatment of the choice in patients with severe mitral stenosis. Brain natriuretic peptide (BNP) has widely applied in cardiology with well established role in heart failure. However, few studies have evaluated this peptide in mitral stenosis, as well the effects of valvuloplasty on BNP levels. The aim of this study was to identify echocardiographic and hemodynamic parameters that determine the changes in BNP levels immediately after percutaneous mitral valvuloplasty in patients with rheumatic mitral stenosis. The study included 19 patients with isolated mitral stenosis who underwent percutaneous balloon mitral valvuloplasty between December 2008 and November 2009. Clinical history, physical exam, electrocardiogram, chest x-ray and transthoracic echocardiogram were obtained in all patients. Exclusion criteria were the presence of atrial fibrillation, left ventricular dysfunction, renal failure, and other associated valve lesions. Right and left heart catheterization was performed in order to measure the hemodynamic parameters before and immediately after the valvuloplasty. BNP serum levels were also obtained before and 24 hours after the mitral valvuloplasty. Of the 19 patients, 18 (95% of the cases) were women. The mean age was 39 ± 9.8 years. The majority of the patients were in functional class II and III of NYHA. Four patients were excluded because they had complications related to the procedure. After the mitral valvuloplasty, there was an increased of the valve area (1.0 ± 0.1 to 1.6 ± 0.2 cm²; p< 0.001) and decreased of mitral valve gradient (14.4 ± 6.0 to 7.1 ± 2.0 mm Hg; p= 0.003). There was also a reduction in the pulmonary pressures, although the index of pulmonary vascular resistance has no decreased significantly (195.3 ± 183.9 to 143.2 ± 91.8 dynas/seg/cm-5/m²; p=0.153). Cardiac output (4.5 ± 0.9 to 5.4 ± 1,1 L/min; p= 0.034) and cardiac index [2.5 (2.2/2.9) to 3.2 (2.6/3.3) L/min/m²; p = 0.031] were increased. The index of systemic vascular resistance decreased (952.4 ± 329.9 to 730.2 ± 188.5 dynas/seg/cm-5/m²; p= 0.036). The index of performance of the right ventricle decreased, but no significantly [13.8 (7.4/21.6) to 10.1 (6.0/24.5) gm/m²; p= 0.084]. There was a tendency of reduction of BNP levels with the valvulopasty [70.6 (41/213) to 52.6 (33/111] pg/ mL, p= 0.087]. Considering the change of BNP levels (delta BNP) as a dependent variable, we found a correlation with these variables which were measure before the procedure: index of pulmonary vascular resistance (r= 0.78; p= 0.002), index of systemic vascular resistance (r= 0.81; p= 0.001), index of performance of the right ventricle (r= 0.53; p= 0.048), mean pulmonary artery pressure (r= 0.72; p= 0.006), and the mitral valve gradient (r= 0.45; p= 0.084). The delta BNP was also correlated with change of the index of pulmonary vascular resistance (r= 0.65; p= 0.015), index of systemic vascular resistance (r= 0.76; p= 0.003), mean pulmonary wedge pressure (r= 0.58, p= 0.031), cardiac index (r= 0.42; p= 0.099), mean pulmonary artery pressure (r= 0.57; p= 0.035), and mean mitral valve gradient (r= 0.47; p= 0.072), and mean aortic pressure (r= 0.79; p= 0.002). In multivariate analysis, independent predictors of delta BNP levels were the index of systemic vascular resistance and the index of performance of the right ventricle. In conclusion, the present study demonstrated that the index of the right ventricular performance and index of systemic vascular resistance were hemodynamic parameters that determined the changes of BNP levels with percutaneous mitral valvuloplasty.